Influenza vaccine strategies for solid organ transplant recipients. Issue 4 (August 2018) - Hirzel, Cédric; Kumar, Deepali
Abstract : Purpose of review: The aim of this study was to highlight recent evidence on important aspects of influenza vaccination in solid organ transplant recipients. Recent findings: Influenza vaccine is the most evaluated vaccine in transplant recipients. The immunogenicity of the vaccine is suboptimal after transplantation. Newer formulations such as inactivated unadjuvanted high-dose influenza vaccine and the administration of a booster dose within the same season have shown to increase response rates. Intradermal vaccination and adjuvanted vaccines did not show clear benefit over standard influenza vaccines. Recent studies in transplant recipients do not suggest a higher risk for allograft rejection, neither after vaccination with a standard influenza vaccine nor after the administration of nonstandard formulation (high-dose, adjuvanted vaccines), routes (intradermally) or a booster dose. Nevertheless, influenza vaccine coverage in transplant recipients is still unsatisfactory low, potentially due to misinterpretation of risks and benefits. Summary: Annual influenza vaccination is well tolerated and is an important part of long-term care of solid organ transplant recipients.